(untitled) (Research, Society and Development, 2022)
The evaluation and work of the teacher, instead, become available for the results observed in the classroom are in line with the proposed objectives and if the teaching-learning process is occurring in content. However, there is still a structure on the part of teachers to adopt other available methods. Thus, this work is a direct study of the practice of science teachers in the. The study is carried out in a public school in the city of Vila Antonico in the city of Quixelô - CE, João Vicente Alves Elementary School. A data collection was performed with a questionnaire application with science teachers. The results are the majority of teachers who answered the questionnaire are still related to tests and exams as an evaluation method. This criterion is available in the application of tests or exams is criticized by most of the scholars in education because it is considered selective and excluding. Given the above, it is evident that as forms adopted for a learning assessment are not varied and there are difficulties in evaluating facts to students. The results are sent to the search methods available in high school.